An Audit To Determine If Needles Used For Intramuscular Injections Are Suitable For Clients, Based On Their Body Mass Index (BMI) - Sheila White; John Goodwin; Izzat Tajjudin (Centre for Recovery and Social Inclusion, 9th Annual Conference, 2024)
Non-Indexed Publication